Penguatan Storytelling Produk Desa Wisata Bakas Kabupaten Klungkung - Hartanti Woro Susianti; Dewa Ayu Made Lily Dianasari; Ni Made Tirtawati; Hanugerah Kristiono Liestiandre; Ida Bagus Putra Negarayana; Ni Luh Nyoman Tri Lilasari; I Gede Gian Saputra Saputra; Dewa Ayu Nyoman Aridayanti (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2022)
Bakas Village is a MKP Study Program assisted village that already has a cooperation agreement. With the concept of Community Base Tourism, finally a tourism village governance has been formed as a result of a joint decision between the official village and the Bakas traditional village. After the establishment of governance, efforts are still needed to strengthen products in the form of storytelling, as part of marketing, so that Bakas Village can develop priority programs for its tourism village products. This community service is in the form of training which consists of two stages. The first stage is in the form of training related to strengthening storytelling how to describe an attraction and managing visitors as well as managing the interpretation of tourist village products. The second stage is in the form of technical training in packaging storytelling for digital-based tourism village products. The results of this community service activity are increasing the understanding of Bakas tourism village managers about the components of tourist village products, managing visitors in tourist villages, and managing tourist village product interpretations, as well as strengthening the ability of managers to provide digital-based storytelling of Bakas Village products.